Feline Foamy Virus Transmission in Tsushima Leopard Cats I/I on Tsushima Island, Japan - AbuEed, Loai; Makundi, Isaac; Miyake, Ariko; Kawasaki, Junna; Minoura, Chisa; Koshida, Yushi; Nishigaki, Kazuo (Viruses, 2023)
Tsushima leopard cats (TLC; Prionailurus bengalensis euptilurus) only inhabit Tsushima Island, Nagasaki, Japan and are critically endangered and threatened by infectious diseases. The feline foamy virus (FFV) is widely endemic in domestic cats. Therefore, its transmission from domestic cats to TLCs may threaten the TLC population. Thus, this study aimed to assess the possibility that domestic cats could transmit FFV to TLCs. Eighty-nine TLC samples were screened, and FFV was identified in seven (7.86%). To assess the FFV infection status of domestic cats, 199 domestic cats were screened; 14.07% were infected. The phylogenetic analysis revealed that the FFV partial sequence from domestic cats and TLC sequences clustered in one clade, suggesting that the two populations share the same strain. The statistical data minimally supported the association between increased infection rate and sex (p = 0.28), indicating that FFV transmission is not sex dependent. In domestic cats, a significant difference was observed in FFV detection in feline immunodeficiency virus (p = 0.002) and gammaherpesvirus1 infection statuses (p = 0.0001) but not in feline leukemia virus infection status (p = 0.21). Monitoring FFV infection in domestic cats and TLC populations is highly recommended as part of TLC surveillance and management strategies.